First Report of Monosporascus cannonballus causing Root Rot and Vine Decline in Watermelon (Citrullus lanatus) in China - Jin, Ying (Plant disease, 2024)
In June 2023, a sudden outbreak root rot and vine decline symptoms was observed during a watermelon (Citrullus lanatus T.) variety demonstration trial located in Taizhou City, Zhejiang Province, China, with an incidence rate ranging from 75% to 100% and an affected area of nearly 2,000 square meters. The disease initially appeared with a rapid and alarming invasion of root rot and vine decline symptoms within watermelon plants. Affected plants exhibited rapid deterioration, showing symptoms of wilting, yellowing and eventual demise, predominantly during the pre-harvest stage. Notably, numerous black, spherical, erumpent perithecia were clearly visible on the watermelon's root epidermis, a characteristic trait of the disease. Symptomatic plant samples were rigorously disinfected with 75% ethanol, and plated on potato dextrose agar medium for incubation at 25°C, successfully isolate two potential strains. These isolates were inoculated in oatmeal agar and incubated in a 25℃ light incubator. After 30 days, mature perithecia, the same as those found on the watermelon's root epidermis, reached a diameter of 500 μm. Each perithecium contained several pear-shaped asci, 56 to 108.5 μm in length and 30.5 to 46.4 μm in width, typically holding 1, rarely 2 ascospores. These characteristics align precisely with the typical strains of Monosporascus cannonballus Pollack and Uecker (1974). Additionally, sequencing the internal transcribed spacer region of ribosomal DNA (ITS) gene (White et al., 1990), large subunit ribosomal RNA (LSU) gene (Rehner and Samuels 1995), and beta-tubulin (TUB) gene (Glass and Donaldson, 1995) were performed. BLAST analysis indicated the highest nucleotide sequence identity with M. cannonballus CBS 586.93 reference sequence (ITS: 100%, JQ771930; TUB: 98.99%, JQ907292). Representative sequences of isolate ZJUP0990-2 from these regions were deposited in GenBank (Accession No.: OR357656 for ITS; OR474500 for LSU; OR365762 for TUB). A multigene phylogenomic analysis (ITS-LSU-TUB) was undertaken to ascertain the exact phylogenetic position of M. cannonballus within the genus Monosporascus. The amalgamation of both morphological and molecular insights consistently reaffirmed the accurate classification of the causative agent as M. cannonballus. To validate the pathogenicity of M. cannonballus, a controlled greenhouse experiment was conducted using watermelon (cv. Nabite) as the subject. Mycelium fragments, harvested from the edge of the colony ZJUP0990-2, were inoculated into oat liquid medium and cultivated under dark conditions at a consistent temperature of 30°C for 7 days. After 20 days, the inoculated plants exhibited root rot and wilting, mirroring the symptoms observed during the field outbreak. In contrast, the control plants did not exhibit any signs of disease. M. cannonballus was successfully re-isolated from the symptomatic roots of the inoculated plants, satisfying Koch's postulates. This experiment was repeated three times. This pathogenic fungus has previously been documented as a menace to melons in various regions including Mexico (Chew-Madinaveitia et al., 2012) and Brazil (Sales et al., 2004), as well as watermelons in Brazil (Sales et al., 2010), northern Mexico (Gaytan-Mascorro et al., 2012), and Saudi Arabia (Karlatti et al., 1997). To our knowledge, this is the first reported presence of M. cannonballus on watermelons in China. This new disease poses a serious threat to watermelon production, potentially leading to severe economic losses and impacting food security